I'll cry instead: Mu suppression responses to tearful facial expressions. (June 2020) - Krivan, Sarah J.; Caltabiano, Nerina; Cottrell, David; Thomas, Nicole A.
Abstract: Tears are a facial expression of emotion that readily elicit empathic responses from observers. It is currently unknown whether these empathic responses to tears are influenced by specific neural substrates. The EEG mu rhythm is one method of investigating the human mirror neuron system, purported to underlie the sharing of affective states and a facilitator of social cognition. The purpose of this research was to explore the mu response to tearful expressions of emotion. Sixty-eight participants viewed happy and sad faces, both with and without tears, in addition to a neutral control condition. Participants first completed an emotion discrimination task, and then an imitation condition where they were required to mimic the displayed expression. Mu enhancement was found in response to the discrimination task, whilst suppression was demonstrated in response to the imitation condition. Examination of the suppression scores revealed that greater suppression was observed in response to happy-tear and sad tear-free expressions. Planned contrasts exploring suppression to neutral faces revealed no significant differences between emotional and neutral conditions. The mu response to neutral expressions resembled that of the happy-tear and the sad tear-free conditions, lending support to the idea that ambiguous emotional expressions require greater sensorimotor engagement. This study provides preliminary evidence for the role of the mirror neuron system in discerning tearful expressions of emotion in the absence of context. Highlights: Ambiguous facial expressions require greater sensorimotor mirroring. Observation tasks can elicit enhancement and execution tasks elicit suppression. Novel paradigm can isolate observation and execution planning. No link between mu suppression and trait empathy.